Povidone Pleurodesis In Bilateral Chylothorax Post Congenital Diaphragmatic Hernia Repair - Jaffrey, Vebster; Abdullah, Muhammad Fadli; Thiyagaraja, Naveena; Bahari, Mughni (Iranian Journal of Pediatric Surgery, 2025)
Chylothorax is a known complication of postoperative congenital diaphragmatic hernia repair in neonates. We herein report a successful povidone pleurodesis for bilateral chylothorax post congenital diaphragmatic hernia repair for a 3.24kg term male baby. He was noted tachypniec and was subsequently intubated soon after birth. Diagnosis of left congenital diaphragmatic hernia was confirm by chest x ray and corrective surgery was done after a period of stabilisation. Post operatively he made a poor recovery and serial chest images show features of effusion. Drains were inserted and fluids drained were confirmed to be chyle. Initially child was treated conservatively. However, due to persistent high output showing signs of refractory to conservative management we decided to use povidone as pleurodesis. During the course of povidone iodine instillation into both chest tubes, the amount of drain was reducing and subsequently child recovered well.